The Analysis of Flouting Maxim in the @Pepekomik comic strip - Dery Purnama Saefudin; Mulyadi Mulyadi; Prima Pantau Putri Santosa (SALEE: Study of Applied Linguistics and English Education, 2023)
The purpose of this study is to classify the utterances of deviation and violation of the cooperative principle proposed by Grice in the Pepekomik comic strip through the utterances expressed by the characters contained in the comic strip. In addition, this research is also intended to find out the types of flouting made. This research is a qualitative descriptive analysis. Researchers used 25 chapters of Pepekomik comic strips taken from the Instagram account @Pepekomik as data sources. The data are utterances from the characters in the comic strip that contain elements of flouting the principle of cooperation. The data taken are a comic chapter that was published in the period April - June 2022. From this study, the author draws a conclusion where there are flouting maxims of cooperative principle, flouting the maxim of quality (6%), flouting the maxim of quantity (14%), flouting the maxim of relevance (23%), and flouting the maxim of manner (57%). Among the four maxims that are flouted, the maxim of manner is the maxim that is most often flouted because in making humor the comic creator uses wordplay and meaning including ambiguity and implied meaning to create humor in his comic creation.